From 1997 to 2025: The Evolving Relevance of 'Ma 6-T Va Crack-Er' in Modern France - Narcis, Stéphane (Global Journal of Cultural Studies, 2025)
This study investigates the continued relevance of Jean-François Richet's Ma 6-T va crack-er in addressing France's persistent socio-political issues related to the banlieues. Combining historical analysis, theoretical frameworks, and comparative film studies, the paper explores how themes of urban segregation, cultural identity, systemic inequality, and youth rebellion remain pressing in 2025. It also examines how successive policy failures and media representations have entrenched negative perceptions of these marginalised communities. Drawing on the works of Hall, Balibar, Wacquant, Gilroy, and Crenshaw, this paper offers a multidisciplinary analysis while proposing policy solutions to address the long-standing issues in the banlieues.